Good reasons for bad behavior: a randomized controlled experiment on the impact of narrative reading and writing on empathic concern, perspective-taking, and attitude - Bientzle, Martina; Eggeling, Marie; Kimmerle, Joachim (Frontiers in Public Health, 2024)
Background: Empathic concern and perspective-taking may contribute to avoiding stigmatization of adverse health behavior. Narrative writing has been shown to be effective in promoting perspectivetaking and empathy. But since narrative writing is time consuming, we tested in the present study narrative reading as an alternative, more parsimonious approach.Methods: In a randomized controlled experiment, we compared writing a narrative text about a fictitious person who displays disapproved of health behavior to reading such a text and to a control condition in which participants wrote about an unrelated topic. With a sample of n=194 participants, we investigated the impact of writing and reading a narrative text on promoting empathic concern and perspective-taking as well as on attitude change.Results: We found that both writing and reading a narrative text about the fictitious character increased empathic concern, F(1, 191)=32.85, p<.001, part. η 2 =0.15, and perspective-taking, F(1,191)=24.76, p<.001, part. η 2 =0.12, more strongly than writing about an unrelated topic. Writing and reading a narrative text also resulted in a more positive attitude toward this person, F(1, 191)=17.63, p<.001, part. η 2 =0.08. Simply reading a narrative text was equally efficient as narrative writing with respect to empathic concern, p=.581, perspective taking, p=.629, and attitude, p=.197.The finding that narrative reading is as effective as narrative writing suggests that the readers appear to be able to comprehend and engage with the story being told.